PEMBUATAN ROTI MANIS DENGAN SUBSTITUSI WORTEL DAN GLUTEN (The Making of Sweet Bread using Carrot and Gluten Substitution ) (UPN VETERAN JAWA TIMUR, 2015)
Abstract Sweet bread is processed products that are the roasting process result of the dough that has been fermented. The process of making sweet bread consists of mixing or stirring, fermentation, shaping and a roasting spit. The addition of carrot flour aims to improve the content of Vitamin A on the sweet bread. This research aims to know the influence of the substitution carrot flour and addition gluten starch to the quality of the sweet bread in the produce. These studies using Factorial Completely Randomized with two factors and two replications. The first factor is substitution of flour carrot (10%, 20%, 30%). The second factor is the addition of gluten (0%, 2%, 4%, 6%). Substitution carrot flour 10 % by the addition of gluten 6 % ( T1G3 ) produce a sweet bread with criteria as follows levels of a protein 20,159 %, levels starch 44,835 %, levels coarse fiber 0,858 %, levels β carotene 3,58 mg / 100g, volume development 192,5 %, size pore 2.3 mm, texture 0,824 mm / g.dt with organolepti value taste test hedonic 209, color test scoring 5.4 and texture 5,45. Keyword : sweet bread, carrot flour, gluten Abstrak Roti manis merupakan produk-produk olahan yang merupakan hasil proses pemanggangan adonan yang telah difermentasi. Proses pembuatan roti manis terdiri dari pencampuran atau pengadukan, fermentasi, pembentukan (make up) dan pemanggangan. Penambahan tepung wortel bertujuan untuk meningkatkan kandungan Vitamin A pada roti manis. Penelitian ini bertujuan untuk mengetahui pengaruh substitusi tepung wortel dan penambahan gluten terhadap kualitas roti manis yang di hasilkan. Penelitian ini mengunakan Rancangan Acak Lengkap (RAL) yang disusun secara faktorial yang terdiri dari 2 faktor dan diulang sebanyak 2 kali ulangan. Faktor I adalah substitusi tepung wortel (10 %, 20 %, 30 %) . Faktor II adalah penambahan gluten (0%, 2 %, 4 %, 6 %) .Substitusi tepung wortel 10 % dengan penambahan gluten 6 % (T1G3) menghasilkan roti manis dengan kriteria sebagai berikut kadar protein 20,159%, kadar pati 44,835 %, kadar serat kasar 0,858 %, kadar β karoten 3,58 mg/100g, volume pengembangan 192,5 %, ukuran pori 2,3 mm, tekstur 0,824 mm/g.dt dengan nilai organoleptik rasa uji hedonik 209, warna uji skoring 5,4 dan tekstur 5,45. Kata kunci : roti manis, tepung wortel, gluten